GEOLOGY AND HAZARD IMPLICATIONS OF THE MARAUNOT NOTCH IN THE PINATUBO CALDERA, PHILIPPINES - Lagmay A.M.F.; Rodolfo K.S.; Siringan F.P.; Uy H.; Remotigue C.; Zamora P.; Lapus M.; Rodolfo R.; Ong J. (My University, 2007)
The 1991 Pinatubo eruption left 5–6 km3 of debris on the volcano slopes, much of which has been mobilized into large lahars in the following rainy seasons. Also during the eruption, collapse, localized in part along preexisting faults, left a caldera 2.5 km in diameter that almost immediately began to accumulate a 1.6 × 108 m3 lake. By 2001, the water had risen to the fault-controlled Maraunot Notch, the lowest, northwestern portion of the caldera rim comprising the physiographic sill of the Caldera Lake. That year, a narrow artificial canal dug into an old volcanic breccia underlying the outlet channel failed to induce a deliberate lake breakout, but discharge from heavy rains in July 2002 rapidly deepened the notch by 23 m, releasing an estimated 6.5 × 107 m3 of lake water that bulked up into lahars with a volume well in excess of 1.6 × 108 m3. Lakes in other volcanoes have experienced multiple breakouts, providing practical motivation for this study. Fieldwork and high-resolution digital elevation models reveal andesites and ancient lacustrine deposits, strongly fractured and deformed along a segment of the Maraunot Fault, a prominent, steeply dipping, left-lateral fault zone that trends N35°–40°W within and parallel to the notch. Seismicity in 1991 demonstrated that the Maraunot Fault is still active. The fault zone appears to have previously been the erosional locus for a large channel, filled with avalanche or landslide deposits of an earlier eruption that were exhumed by the 2002 breakout floods. The deformed lacustrine sediments, with an uncalibrated 14C age of 14,760 ± 40 year BP from a single charcoal sample, attest to the existence of an earlier lake, possibly within the Tayawan Caldera, rim remnants of which survive as arcuate escarpments. That lake may well have experienced one or more ancient breakouts as well. The 2002 event greatly reduced the possibility of another such event by scouring away the erodible breccia, leaving less erodible fractured andesites and lacustrine rocks, and by enlarging the outlet channel and its discharge capacity. Several lines of evidence indicate, however, that future lahar-generating lake breakouts at the notch may keep populations of Botolan municipality downstream at risk: (1) a volume of 9.5 × 107 m3 of lake water remains perched 0.8 km above sea level; (2) seismicity in 1991 demonstrated that the Maraunot Fault is still active and movements of sufficient magnitude could enlarge the outlet and the discharge through it; (3) more likely, however, with or without earthquake activity, landslides from the steep to overhanging channel walls could block the channel again, and a major rainstorm could then cause a rise in lake level and sudden breakouts; (4) intrusion of a new dome into the bottom of the lake, possibly accompanied by phreatic explosions, could expel large volumes of lahar-generating water.
Keywords: MARAUNOT NOTCH; MARAUNOT FAULT; PINATUBO; CALDERA LAKE; LAKE BREAKOUT; DEBRIS FLOWS; LAHARS